1996
DOI: 10.1002/elan.1140081216
|View full text |Cite
|
Sign up to set email alerts
|

Study of the reduction of palladium(II) on a mercury electrode in the presence of dimethylglyoxime

Abstract: The adsorptive behavior of Pd" ions in the presence of dimethylglyoxime (DMG) was investigated using voltammetric techniques. It was found that the bis-dimethylglyoximato palladium(ii) complex is adsorbed strongly between pH 3 and 5 and between the potentials 0 and -0.3 V (vs. Ag/AgCl). The peak current is proportional to the Pd-DMG surface concentration, and increases linearly with scan rate (Blog i,,/L?u = 0.97). The adsorptive stripping response was evaluated with respect to pH, the concentration of the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Investigation of the reduction process of Pd-DMG complex [14] showed that the voltammetric peak height depends on pH , the concentration of DMG and buffer composition, the scan rate, and the presence of surface active substances [2].The adsorptive stripping response was evaluated with respect to the concentration of the supporting electrolyte and the preconcentration potential. The optimum concentration of the supporting electrolyte (acetate buffer) is 0.1 mol/L and the optimum pH value is 3.5 ± 0.5.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Investigation of the reduction process of Pd-DMG complex [14] showed that the voltammetric peak height depends on pH , the concentration of DMG and buffer composition, the scan rate, and the presence of surface active substances [2].The adsorptive stripping response was evaluated with respect to the concentration of the supporting electrolyte and the preconcentration potential. The optimum concentration of the supporting electrolyte (acetate buffer) is 0.1 mol/L and the optimum pH value is 3.5 ± 0.5.…”
Section: Resultsmentioning
confidence: 99%
“…The optimum potential range for its accumulation is between 0 and -0.35 V with respect to the Ag/AgCl electrode [2,14]. Current response during the reduction of the Pd-DMG complex depends on their equilibrium concentration on the electrode surface [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a technique has been employed for the determination of several metals, but, considering only the platinum group metals, their voltammetric determination is limited to few but definite procedures, procedures, however prevalently addressed to single elements of the PGMs [68,69], so much so that, for example, the same supporting electrolyte may present, at the same potential, voltammetric signals relevant to two different PGMs, as Pt(II) and Ru(III) in the presence of 1-(2-pyridylazo-2-naphtol) as ligand [70]. Evidently, this goes against the peculiarity of the same technique, that permits to quantify simultaneously several metals carrying out single potential scans (possibility of multicomponent determination).…”
Section: Adsorptive Stripping Voltammetry (Adsv)mentioning
confidence: 99%